The application of Vavilov’s approaches to the phylogeny and evolution of cultivated species of the genus Avena L. - I. G. Loskutov; A. A. Gnutikov; E. V. Blinova; A. V. Rodionov (Вавиловский журнал генетики и селекции)
The central problem that Vavilov was investigating was the overall concept of global plant genetic resources. The theoretical basis of this concept consisted of the law of homologous series in variation, research on the problem of species as a system, botanical and geographical bases of plant breeding, and the key theory of the centers of origin of cultivated plants. The VIR global collection of plant genetic resources collected by Vavilov and his associates from all over the world reflects the fullness of botanical, morphological and genetic diversity, and can be used for historical, evolutionary, phylogenetic and applied breeding research aimed at unlocking the potential of all the collection material. The whole diversity of cultivated oats, as was proved by Vavilov, had originated from segetal weeds. This process can be clearly traced in Spain on the example of the cultivated diploid species A. strigosa, A. abyssinica in Ethiopia, A. byzantina in Turkey and Iran, and on segetal forms of A. sativa. The studies of the morphological features as a whole do not yield a complete picture of the evolutionary and systematic status of some oat species and forms. The methods and approaches that use DNA markers and genomic technologies, and are promising for the study of oat polymorphism and phylogeny have been actively researched recently. A number of works devoted to the molecular aspects of the evolution and phylogeny of the genus Avena have recently appeared. The research uses various markers of genes, gene regions, intergenic spacers (internal and external), both nuclear and chloroplast and mitochondrial, genomic approaches and other modern methods. On the basis of a comprehensive study of the complete intraspecific diversity from different zones of the distribution range of cultivated oat species as well as on the basis of an analysis of data on the geography of forms and species distribution ranges, it was established that the process of hexaploid species formation also took place in the western part of the Mediterranean, and subsequently, when moving eastward, these forms started occupying all the vast spaces in the region of the Southwest Asian center, forming a large intraspecific diversity of wild forms and weedy ones in transit to cultivated hexaploid oat species. An analysis of the intraspecific diversity of landraces has specified the centers of morphogenesis of all cultivated oat species. The phylogenetic analysis of the representative intraspecific diversity of cultivated and wild Avena species carried out using next generation sequencing (NGS) showed that diploid species with A-genome variants are in fact not primary diploids, but a peculiar Mediterranean introgressive hybridization complex of species that sporadically enter into interspecific hybridization. It was established that the tetraploid cultivated species A. abyssinica had most likely originated from the wild A. vaviloviana. An analysis of the ways of A. sativa and A. byzantina domestication showed that the most widespread ribotype of the A. sativa hexaploid was inherited from A. ludoviciana, and the second most widespread one, from A. magna, while A. byzantina has two unique ribotype families, most likely inherited from an extinct oat species or a still undiscovered cryptospecies.